Collagenase Treatment of Dupuytren's Disease with Minimum 5-Year Follow-Up: Recurrence, Reintervention, and Satisfaction. Issue 5 (November 2020) - Zhang, Dafang; Earp, Brandon E.; Benavent, Kyra A.; Blazar, Philip
Abstract : Background: The objective of this study was to determine the rates of patient satisfaction, perceived recurrence of flexion deformity, and additional treatment after collagenase clostridium histolyticum treatment for Dupuytren's contracture at a minimum of 5-year follow-up. Methods: A retrospective study was performed of 199 digits in 142 patients who underwent collagenase clostridium histolyticum treatments from April of 2010 to December of 2013 with a minimum of 5-year follow-up. Patients were contacted by telephone regarding perceived recurrence, additional treatment, satisfaction, and willingness to undergo this treatment again. Results: At an average 7.2-year follow-up, 160 of 199 digits (80 percent) had perceived recurrence, and 105 of 199 digits (53 percent) underwent additional treatment. Average satisfaction was 6.5 on a Likert scale ranging from 1 to 10, and 67 percent would undergo collagenase clostridium histolyticum treatment again. Multivariable logistic regression analysis showed that higher Charlson Comorbidity Index (OR, 0.77; 95 percent CI, 0.63 to 0.93) and isolated metacarpophalangeal joint involvement (OR, 0.53; 95 percent CI, 0.29 to 0.97) were associated with decreased odds of additional treatment, and higher American Society of Anesthesiologists physical status classification (OR, 2.49; 95 percent CI, 1.35 to 4.48) and nonsmoker status (OR, 0.23; 95 percent CI, 0.09 to 0.59) were associated with willingness to undergo the treatment again. Conclusions: Patients may be counseled that the long-term perceived recurrence rate of Dupuytren's contractures after collagenase clostridium histolyticum treatment is high, and more than half of patients seek additional treatment. Satisfaction and willingness to undergo collagenase clostridium histolyticum treatment decrease with perceived recurrence. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.